Choosing the optimal bandwidth in case of correlated data - Klaus Brachmann (University of Cologne, Seminar of Economic and Social Statistics, 1995)
In case of estimating growth curves nonparametrically onc faces the fact that the data driven bandwidth selectors published in standard textbooks mostly choose bandwidths much too low. This is due to the positive autocorrelation observed in growth data. This paper introduces an easy way to incorporate this effect in the known concept of penalizing functions.
Keywords: 330